Development Strategy of Madasari Beach Marine Tourism, Pangandaran Regency, Indonesia - Prihadi, Donny Juliandri; Annida, Shafira Bilqis; Kristiadhi, Fanny; Dhahiyat, Ahmad Prawira; Junirahma, Nur Sakinah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Madasari Beach has an advantage with its beautiful natural panorama. Madasari Beach is a marine tourism that was only developed in 2018 and is relatively new. So, it is necessary to develop marine tourism on Madasari Beach. This study aims to identify and determine the potential on Madasari Beach. The method used in this study is the SWOT method analyzing the internal and external factors of marine tourism on Madasari Beach through the IFAS and EFAS matrix, SWOT Diagram, and SWOT Analysis Table. The results indicate that marine tourism on Madasari Beach supports aggressive strategies where there are 9 alternative strategies in the development of marine tourism on Madasari Beach.